The Effect of Capital Structure on Stock Returns in Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period - William Tjong; Rion Kurniawan (Institute of Computer Science (IOCS), 2021)
This research is entitled The Effect of Capital Structure on Share Earnings in Companies Listed on The Indonesia Stock Exchange for The 2015-2019 Period. This journal analyzes the effect of capital structure on stock returns in Indonesia. Where capital structure can be regarded as one of the factors that can explain stock returns. The data used in the study are companies that have been listed on the Kompas 100 index on the Indonesia Stock Exchange (IDX) in Indonesia which publish periodic financial reports from 2015 to 2019, the data used is time series data, data obtained from yahoo finance , and the Indonesia Stock Exchange website. The results showed that the capital structure has no significant effect on stock returns, but other control variables such as earnings per share, return on assets and size have a significant effect on stock returns.